Language and regional identity - Eichinger, Ludwig M. (2008)
Europe is a continent of many languages. We all know that, but normally when we think about this fact, we focus on national languages, the type of language that shapes our political and our linguistic geography. But as natural as it may seem today, the idea of a language closely being interrelated with one's identity does not have a very long tradition. In fact it is only since the late 18th century that we think there is some type of intimate connection between the language spoken and the identity of a person as belonging to a nation. And even if the stabilization of European nation states was closely connected with this type of reasoning, European language communities differ considerably in their way of dealing with natural variation within their national language. For some of them, it is only the standardized national language that is relevant in this respect; for others, a certain amount of variation is a central part of their linguistic identity.
https://creativecommons.org/licenses/by-nc-nd/3.0/de/deed.de ; info:eu-repo/semantics/openAccess
Keywords: Deutsch; Standardsprache; Dialekt; Identität